Comparison of official and friendly matches through acceleration, deceleration and metabolic power measures: a full-season study in professional soccer players - Nobari, Hadi (2021)
Soccer is a popular team sport and highly demanding activity that requires high effort and long-term training plans. The goals of this study were to compare the accelerations, decelerations and metabolic power between official and friendly full matches, between the first and second halves of the matches, and between both halves of official and friendly matches. Twelve professional soccer players (age, 28.6 ± 2.7 years; height, 182.1 ± 8.6 cm; body mass, 75.3 ± 8.2 kg; BMI, 22.6 ± 0.7 kg/m2) participated in this study. A total of 33 official and 10 friendly matches were analyzed from the Iranian Premier League. All matches were monitored using GPSPORTS systems Pty Ltd. The following variables were selected: total duration of the matches, metabolic power, accelerations Zone1 (<2 m·s-2) (AccZ1), accelerations Zone2 (2 to 4 m·s-2) (AccZ2), accelerations Zone3 (>4 m·s-2) (AccZ3), decelerations Zone1 (<-2 m·s-2) (DecZ1), decelerations Zone2 (-2 to -4 m·s-2) (DecZ2) and decelerations Zone3 (>-4 m·s-2) (DecZ3). The major finding was shown in metabolic power, where higher values occurred in friendly matches (p < 0.05 with small effect size). Furthermore, total duration, AccZ3, DecZ1, DecZ2, and DecZ3 were revealed to be higher in official matches, while AccZ1 and AccZ2 were higher in friendly matches. The second half of the official matches revealed higher values for total duration compared to friendly matches (p < 0.05, moderate effect size). In conclusion, this study observed higher values of metabolic power in friendly matches compared to official matches. AccZ3, DecZ1, DecZ2, and DecZ3 were higher in official matches, while AccZ1 and AccZ2 were higher in friendly matches.